Trust your gut or think carefully? Examining whether an intuitive, versus a systematic, mode of thought produces greater empathic accuracy. [article]. - Ma-Klemmas, Christine
Cultivating successful personal and professional relationships requires the ability to accurately infer the feelings of others-that is, to be empathically accurate. Some are better at this than others, a difference which may be explained in part by mode of thought. Specifically, empathically accurate people may tend to rely more on intuitive rather than systematic thought when perceiving others. Or it may be the reverse: systematic thought may increase empathic accuracy. To determine which view is supported by the evidence, we conducted 4 studies examining relations between mode of thought (intuitive vs. systematic) and empathic accuracy. Study 1 revealed a lay belief that empathic accuracy arises from intuitive modes of thought. Studies 2 through 4, each using executive-level professionals as participants, demonstrated that, contrary to lay beliefs, people who tend to rely on intuitive thinking also tend to exhibit lower empathic accuracy. This pattern held when participants inferred others' emotional states based on (a) in-person face-to-face interactions with partners (Study 2) as well as on (b) pictures with limited facial cues (Study 3). Study 4 confirmed that the relationship is causal: experimentally inducing systematic (as opposed to intuitive) thought led to improved empathic accuracy. In sum, evidence regarding personal and social processes in these 4 samples of working professionals converges on the conclusion that, contrary to lay beliefs, empathic accuracy arises more from systematic thought than from gut intuition. -- (from the authors)